Manajemen Konflik Internal dalam Organisasi Studi Kasus pada PT. Ruyung Karya Mandiri - Nauval Buya Dwi andhika; Muhammad Fauzan Adhima Subianto; Sentot Imam Wahjono (Journal of Innovative and Creativity, 2025)
In a dynamic and competitive organizational environment, internal conflict is an unavoidable challenge that can significantly affect company performance. This study aims to identify the causes of internal conflict, the types of conflicts that occur, their impact on organizational performance, and strategies for managing them constructively. Using a qualitative approach with a case study method, the research was conducted at PT. Ruyung Karya Mandiri, a manpower service company. The findings reveal that internal conflicts arise from dissatisfaction with compensation, cultural differences between local employees and expatriates, and the lack of employee involvement in decision-making processes. These conflicts negatively impact productivity, employee loyalty, and operational effectiveness. However, through strategies such as cross-cultural training, employee involvement, and human resource mapping, conflicts can be managed as opportunities to improve work systems and enhance organizational performance. This study highlights the importance of strategic and adaptive conflict management in maintaining organizational stability.